A survey of adaptive large neighborhood search algorithms and applications. (October 2022) - Windras Mara, Setyo Tri; Norcahyo, Rachmadi; Jodiawan, Panca; Lusiantoro, Luluk; Rifai, Achmad Pratama
Highlights: This article presents survey on the adaptive large neighborhood search (ALNS). We consider 252 research articles related to ALNS from 2006 to 2021. The analysis of ALNS developments and applications are based on taxonomical review. Structure, hybridization, optimization class, and application area are discussed. Research directions are highlighted for future work. Abstract: This article provides a survey on the highly popular metaheuristic framework, the adaptive large neighborhood search (ALNS). The basic concepts of ALNS are discussed in this paper. Based on a simple taxonomy, the analysis of publication intensity, application areas, and the variant of ALNS features are executed on 252 scientific publications to synthesize the state-of-the-art of ALNS research. Finally, some discussions on the future research of ALNS are provided.